Humoral response to SARS-CoV-2 is well preserved and symptom dependent in kidney transplant recipients - Magicová, Mária; Fialova, Martina; Zahradka, Ivan; Rajnochova-Bloudickova, Silvie; Hackajlo, David; Raska, Petr; Striz, Ilja; Viklicky, Ondrej (American journal of transplantation, 2021)
Data on the immune response to SARS-CoV-2 in kidney transplant recipients are scarce. Thus, we conducted a single-center observational study to assess the anti-SARS-CoV-2 IgG seroprevalence in outpatient kidney transplant recipients (KTR; n = 1037) and healthcare workers (HCW; n = 512) during the second wave of the COVID-19 pandemic in fall 2020 and evaluated the clinical variables affecting antibody levels. Antibodies against S1 and S2 subunit of SARS-CoV-2 were evaluated using immunochemiluminescent assay (cut off 9.5 AU/ml, sensitivity of 91.2% and specificity of 90.2%). Anti-SARS-CoV-2 IgG seroprevalence was lower in KTR than in HCW (7% vs. 11.9%, p = .001). Kidney transplant recipients with SARS-CoV-2 infection were younger (p = .001) and received CNI-based immunosuppression more frequently (p = .029) than seronegative KTR. Anti-SARS-CoV-2 IgG positive symptomatic KTR had a higher BMI (p = .04) than asymptomatic KTR. Interestingly, anti-SARS-CoV-2 IgG levels were higher in KTR than in HCW (median 31 AU/ml, IQR 17-84 vs. median 15 AU/ml, IQR 11-39, p < .001). The presence of moderate to severe symptoms in KTR was found to be the only independent factor affecting IgG levels (Beta coefficient = 41.99, 95% CI 9.92-74.06, p = .011) in the multivariable model. In conclusion, KTR exhibit a well-preserved symptom-dependent humoral response to SARS-CoV-2 infection.
Keywords: transplantace ledvin; protilátky virové; pandemie; lidé; příjemce transplantátu; Transplant Recipients; SARS-CoV-2; séroepidemiologické studie; Antibodies, Viral; Kidney Transplantation; Pandemics; Seroepidemiologic Studies; COVID-19; Humans